Establishing an appeal mechanism for investor-state dispute settlement : challenges, feasibility, and options - Xi, Zhang; Rozanah Ab Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
There is a growing international consensus stating investor-state dispute settlement mechanism (ISDS), with international investment arbitration as the main means of dispute settlement, needs to be reformed, but the reform proposals have not yet been finalised. Among the many options, the option of establishing an appeal mechanism has generated extensive discussion. The permanent, independent and corrective nature of the appeals mechanism helps to address the lack of independence and impartiality of arbitrators under the ISDS mechanism, the inconsistency of arbitral awards, and the lack of control mechanisms. It also has benefit of improving the accuracy of awards. Under the current system of international investment treaties, establishing a multilateral appeal mechanism presents many challenges. However, the Mauritius Convention on Transparency, which uses multilateral instruments to amend bilateral treaties, provides evidence that establishing a multilateral appeal mechanism is feasible.